A CLINICAL STUDY OF URTICARIA AND ANGIOEDEMA WITH PARTICULAR REFERENCE TO THE ETIOLOGY - Rakesh M Patel; Roshni A Vohra; Kiran K Chotaliya; Ankit H Bharti; Maulik Shinojia (National Journal of Medical Research, 2014)
Introduction: Urticaria is one of the most distressing, frustrating and challenging dermatological condition for both patients and doctors as well. The aim of present study is to find out causes of urticaria, age and sex distribution and association with atopy and other systemic diseases.